Performance assessment a teacher's way of knowing - Meisels, Samuel J.; Davidson Films (San Luis Obispo, CA : Davidson Films, 1993)
Explains the principles of performance assessment using illustrations from a Head Start program and kindergarten and third grade classes of a public school.
Samuel J. Meisels.
DVD.
Keywords: Education -- Evaluation -- United States; Educational tests and measurements -- United States